TUD-1 type aluminosilicate acid catalysts for 1-butene oligomerisation. (1st December 2017) - Silva, Andreia F.; Fernandes, Auguste; Antunes, Margarida M.; Neves, Patrícia; Rocha, Sílvia M.; Ribeiro, Maria F.; Pillinger, Martyn; Ribeiro, Jorge; Silva, Carlos M.; Valente, Anabela A.
Graphical abstract: Abstract: TUD-1 type mesoporous aluminosilicates were explored for the acid-catalysed oligomerisation of 1-butene, under high pressure, continuous flow operation, which is an attractive route to produce sulphur-free synthetic fuels with reduced aromatics content. The solid acid catalysts were synthesised via one-pot synthesis (HT) or stepwise approach (PG), without using surfactants as templates, which is an eco-friendly characteristic of the TUD-1 family. While the HT approach may be advantageous in terms of process intensification in relation to the PG one, the latter may lead to relatively low molar ratios Si/Al. The catalysts possessed Si/Al ratios in the range 3–5 and 17–35 for the PG and HT approaches, respectively, pore sizes in the range 10–14 nm, and essentially Lewis acidity. To the best of our knowledge, this is the first report of siliceous oxide TUD-1 furnished with acidity via post-synthesis grafting (PG) of Al-species. For comparative studies, an ordered mesoporous aluminosilicate was synthesised via the PG approach using surfactant mixtures. All materials prepared promoted the reaction of 1-butene to higher molar mass products. The best-performing catalyst in terms of space-time yields of the 170–390 °C cut (boiling point range) products (of the type middle distillates) was Al-TUD-1(25)-HT synthesised via the HT method. The products were analysed by comprehensive two-dimensional gas chromatography (GC × GC) combined with time-of-flight mass spectrometry (ToFMS). The influence of material properties and process parameters on the catalytic reaction, and catalyst stability were studied. The catalytic performances were benchmarked with ZSM-5 (zeolite used in commercial oligomerisation processes).